Prevalence of per- and polyfluoroalkyl substances (PFASs) in marine seafood from the Gulf of Guinea - Abraham Ogheneruemu Ekperusi; Nadège Bely; Charles Pollono; Kélig Mahé; Catherine Munschy; Yann Aminot (Chemosphere, 2023)
PFASs are ubiquitous in the global environment due to their wide use, persistence and bioaccumulation, and are of concern for human health. This study investigated the levels of PFASs in seafood with a view to provide knowledge on the occurrence of PFASs in marine resources and to evaluate seafood safety and human health risk via dietary exposure to coastal communities in the Gulf of Guinea, where there is currently very little data. The sum of targeted PFASs was between 91 and 1510 pg g-l ww (mean 465 ± 313 pg g-l ww), with PFOS and long-chain PFCAs prevailing. The concentrations of PFASs in the three species of croakers were species- and location-dependent, with habitat and anthropogenic pressure as likely drivers of the differences. Significantly higher contamination levels were found in male croakers. The trophic transfer and biomagnification of PFASs from shrimps to croakers was evidenced for PFOS and long-chain PFCAs (with a significant increase of contaminants from the prey to the predator). The calculated estimated daily intakes (EDIs) and hazard ratio (HR) for PFOS in croakers (whole fish and muscles) and shrimp were lower than the European Food and Safety Agency's recommended level for PFOS (1.8 ng kg−1 day−1) and below the HR safety threshold value of 1. From the results, based on present safety limits, PFOS levels in croakers and shrimps from the Gulf of Guinea do not pose immediate health risks to the human population. This study provides the first insight regarding the distribution of PFASs in seafood from the tropical NE Atlantic region of the Gulf of Guinea and highlights the need for further monitoring across the Gulf.
Keywords: PFAS; Gulf of Guinea; Emerging contaminants; Seafood; Environmental monitoring; estimated daily intake; risk assessment